High-thermal-conductivity In-Pb-X alloy low-temperature soldering paste and preparation method thereof
Spherical powder is prepared by a combined atomization method of inert gas atomization and high-speed centrifugal rotation, and neutral acid anhydride flux and coating agent are used to solve the oxidation and fluidity problems of indium-based solder paste, and achieve stable suspension and rapid activation of high thermal conductivity, low-temperature solder paste, which is suitable for a variety of welding processes.
Patent Information
- Application Number
- CN202510922974.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-04
- Publication Date
- 2025-10-03
AI Technical Summary
The existing indium-based solder paste has problems such as powder surface oxidation, low sphericity, poor fluidity and short shelf life during the preparation process, and traditional flux causes the solder paste to be unable to flow and wet.
Spherical powder is prepared by inert gas atomization + high-speed centrifugal rotation combined atomization method, neutral substances are ultrasonically coated, neutral anhydride flux and matching flux are used, and vacuum centrifugal degassing is used to prepare the paste without contact at low pressure to ensure that the alloy powder is stably suspended at low temperature and quickly activated during the brazing process.
The high thermal conductivity In-Pb-X alloy low-temperature solder paste is stably suspended at low temperatures, quickly activated during welding, has little residue after welding, is suitable for a variety of welding processes, has good wettability and fluidity, has few weld defects, and can be stored in a refrigerated container for more than 6 months.
Smart Images

Figure CN120734580A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic packaging technology, in particular to the field of microsystem electronic packaging technology, and specifically relates to a high thermal conductivity In-Pb-X alloy low-temperature solder paste and a preparation method thereof. Background Art
[0002] Indium has good ductility and malleability, allowing it to be deformed and fill even tiny uneven gaps between two mating parts using only moderate pressure. This ductility and malleability are maintained even at ultra-low temperatures, allowing the assembly to remain effectively sealed even in harsh environments. Indium has a high thermal conductivity (86 W / mK at 85°C), so it is widely used in thermal management applications to dissipate heat generated by electronic components. When bonding different components, indium can compensate for the different coefficients of thermal expansion (CTE). Even small amounts of indium can improve the thermal fatigue performance of solders used in electronic assembly. Some indium-containing alloys have a melting point below 180°C, making them ideal for multiple soldering cycles or soldering requiring lower reflow temperatures. Indium has a low vapor pressure, making it suitable for high-vacuum soldering. Indium alloy solders have shown better resistance to drop tests than other low-melting-point alloys.
[0003] The difficulties in preparing indium-based solder paste mainly lie in the fact that the mechanical properties of indium-based alloys are lower than those of other soft solder materials, and they are easily deformed and oxidized by external factors, resulting in a dense indium oxide (In2O3) film on the surface of the powder, which leads to a low powder ball-forming rate, irregular sphere morphology, and poor fluidity. In the process of preparing solder paste, the alloy powder is further deformed by the stirring force. Traditional rosin-type flux has an effective film-breaking effect on indium-based solder powder brazing, resulting in the solder paste being unable to flow and wet. Although acidic flux can quickly react with the powder surface film, it causes the alloy powder in the paste to agglomerate and coarsen in a short time, greatly shortening the shelf life of the solder paste. Summary of the Invention
[0004] The main purpose of the present invention is to provide a high thermal conductivity In-Pb-X alloy low-temperature solder paste, which has a high melting temperature, good wettability to metal coatings, is non-corrosive, and leaves little residue after soldering.
[0005] Another object of the present invention is to provide a method for preparing the high-thermal-conductivity In-Pb-X alloy low-temperature solder paste. To address the aforementioned issues with indium-based solder paste in the prior art, the present invention systematically analyzes all grades of indium-based alloy low-temperature series and develops a combined atomization process of "inert gas atomization + high-speed centrifugal rotation" to achieve spherical powder preparation. The invention also pioneers a design for ultrasonically coating the powder surface with a neutral substance, which is then prepared into a paste using a developed matching flux through contactless, low-pressure vacuum centrifugal degassing. The flux's main active substance is a neutral acid anhydride, such as methyltetrahydrophthalic anhydride, hexahydro-4-methylphthalic anhydride, methylnadic anhydride, dodecenylsuccinic anhydride, and succinic anhydride. These are stable at room temperature and rapidly decompose during the brazing process to produce highly activated acidic substances that react with the indium-based surface film, allowing the molten alloy to rapidly undergo brazing reaction with the substrate. The coating agent is a sodium citrate and isopropyl alcohol solution, which is easily decomposed and volatilized during the active reaction phase before brazing, preventing any residue from remaining in the solder joint.
[0006] To achieve the above object, the present invention adopts the following design scheme:
[0007] A high thermal conductivity In-Pb-X alloy low-temperature solder paste, composed of the following components by weight percentage:
[0008] Solder alloy powder 80.0wt% to 90.0wt%;
[0009] Highly active flux 6.0wt% to 10.0wt%;
[0010] Coating agent 4.0wt% to 10.0wt%;
[0011] The total amount of the above components is 100%;
[0012] The solder alloy powder comprises, by weight percentage, 14.0-41.0 wt% Pb, 0-10 wt% X, and the remainder In, wherein the X element is one or more of Sn, Ag, Au, Bi, Sb, and Cu, and the total amount of the above components is 100%.
[0013] Furthermore, the solder alloy powder has a composition, by weight percentage, of Pb: 15.0-35.0 wt%, 15.0-32.0 wt%, X: 1-10 wt%, preferably 3-10 wt% or 3-5 wt%, and the balance is In.
[0014] Furthermore, the highly active soldering flux is composed, by weight percentage, of a mixture of 5% to 10% of an active agent, 5% to 10% of a surfactant, 2% to 8% of a paste-forming agent, 20% to 30% of a wetting agent, 2% to 5% of a thixotropic agent and 40% to 65% of a solvent.
[0015] In the soldering flux, the activator is a neutral acid anhydride, including one of methyltetrahydrophthalic anhydride, hexahydro-4-methylphthalic anhydride, methyl nadic anhydride, dodecenylsuccinic anhydride and succinic anhydride; the surfactant is stearic acid amide; the paste-forming agent is hydroxyethyl cellulose; the wetting agent is cocoamidopropyl betaine; the thixotropic agent is a PLUS thixotropic agent; and the solvent is hydrogenated rosin solution (preferably at a concentration of 50wt%) + malic acid, wherein the malic acid is 5wt.%.
[0016] Furthermore, the coating agent is composed of a mixture of 35-38% sodium citrate and 62-65% low boiling point solvent in terms of weight percentage.
[0017] In the coating agent, the low boiling point solvent is one of isopropyl alcohol, methanol, hexachloroethane and cyclopentyl methyl ether.
[0018] The solder alloy powder paste prepared from the flux and solder alloy powder can be evenly suspended in the flux and maintained at low temperatures (below 20°C) for six months without sedimentation and is not easily oxidized. The flux evaporates slowly at room temperature and rapidly at soldering temperatures, leaving little residue. The flux is moderately active, effectively transferring heat and significantly reducing the surface tension of the molten solder.
[0019] A method for preparing a high thermal conductivity In-Pb-X alloy low-temperature solder paste comprises the following steps:
[0020] (1) Solder alloy smelting: prepare the materials according to the following weight percentages: Pb: 14.0-41.0 wt%, X: 0-10 wt%, In as the balance, where X is one or more of Sn, Ag, Au, Bi, Sb, and Cu, and use non-vacuum electromagnetic stirring smelting and rapid cooling continuous casting to obtain the alloy;
[0021] (2) Preparation of solder alloy powder: The alloy prepared in step (1) is atomized to obtain spherical alloy powder by using a combined atomization method of "inert gas atomization + high-speed centrifugal rotation", and then an inert gas flow separation method is used to obtain alloy powders of different particle size ranges;
[0022] (3) Preparation of high-activity soldering flux: Prepare the materials by weight percentage, 5% to 10% of active agent, 5% to 10% of surfactant, 2% to 10% of paste-forming agent, 20% to 30% of wetting agent, 2% to 5% of thixotropic agent and 40% to 65% of solvent, add the active agent, surfactant, paste-forming agent, wetting agent and thixotropic agent to the solvent, heat and stir, mix until completely dissolved, and let it stand to prepare the soldering flux;
[0023] (4) Preparation of coating agent: Prepare the materials according to weight percentage, add 35-38% sodium citrate into 62-65% isopropyl alcohol, stir with ultrasonic, and after complete dissolution, mix evenly and let stand to prepare the coating agent;
[0024] (5) Preparation of solder paste: The alloy powder obtained in step (2) is immersed in the coating agent obtained in step (4), and the surface of the alloy powder is fully coated using ultrasonic assistance; then the high-activity flux obtained in step (3) is added in proportion, and the coated powder and the flux are mixed evenly in a contactless and low-pressure manner using a vacuum degassing centrifugal stirring method to obtain a high thermal conductivity In-Pb-X alloy low-temperature solder paste.
[0025] In step (1), when the solder alloy is melted, a non-vacuum medium-frequency induction continuous casting furnace is used for melting the solder alloy, with a heating power of 10 to 15 kW, a refining temperature of 300 to 350° C., a refining time of 20 to 30 min, and a fast cooling crystallizer made of high-density graphite.
[0026] In step (2), when preparing the solder alloy powder, the atomization method is "inert gas atomization + high-speed centrifugal rotation" combined atomization, the atomization temperature is 300°C to 340°C, the inert gas is high-purity argon, the atomizing gas pressure is 0.2MPa to 0.5MPa, the centrifugal speed is 1000 to 2000n / min, and the atomizing disk is 316L stainless steel.
[0027] In step (2), the alloy powder obtained by atomization is separated by an inert gas flow to obtain alloy spherical powders with different particle size ranges of No. 3 (25-45 microns), No. 4 (20-38 microns), No. 5 (15-25 microns), and No. 6 (10-20 microns).
[0028] In step (3), the active agent is a neutral acid anhydride, including one of methyltetrahydrophthalic anhydride, hexahydro-4-methylphthalic anhydride, methyl nadic anhydride, dodecenylsuccinic anhydride, and succinic anhydride; the surfactant is stearic acid amide; the paste-forming agent is hydroxyethyl cellulose; the wetting agent is cocoamidopropyl betaine; the thixotropic agent is PLUS thixotropic agent; and the solvent is hydrogenated rosin solution (concentration is 50%) + malic acid (wherein the malic acid is 5%).
[0029] In step (3), when the soldering flux is prepared, the heating temperature is 50°C to 70°C.
[0030] In step (4), the coating agent is prepared by mixing 35-38% sodium citrate and 62-65% isopropyl alcohol. When the coating agent is prepared, the ultrasonic frequency is 80-100 KHz.
[0031] In step (5), the solder paste preparation method is to firstly perform ultrasonic coating on the alloy powder, with an ultrasonic frequency of 100 to 120 kHz and a time of 15 to 30 min; then, the alloy powder is centrifuged and stirred with the flux by vacuum degassing to prepare the paste, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 800-1200 rpm, stirring time 10-20 min, prepare the alloy solder paste, and put it into a plastic jar or syringe.
[0032] The high thermal conductivity In-Pb-X alloy low-temperature solder paste of the present invention is suitable for use in a variety of soldering processes, including soldering processes for electronic components, surface mount components, and electronic circuit assembly.
[0033] Advantages of the present invention:
[0034] 1. The high thermal conductivity In-Pb-X alloy low-temperature solder paste manufactured by the method of the present invention is suitable for a variety of welding processes, including electronic components, surface mount components and special welding processes for electronic circuit assembly.
[0035] 2. The high thermal conductivity In-Pb-X alloy manufactured by the method of the present invention basically covers the melting temperature of 130 to 200°C.
[0036] 3. The high thermal conductivity In-Pb-X alloy low-temperature solder paste manufactured by the method of the present invention has good welding processability, good wettability and fluidity, few weld defects and high reliability.
[0037] 4. The coating agent design in the low-temperature solder paste manufactured by the method of the present invention after welding cleaning avoids the drying and coarsening phenomena that occur during the stirring and storage process of the indium-based solder paste; the activator adopts a neutral acid anhydride, which is stable at room temperature. During the brazing process, it quickly decomposes the acidic highly activated substance, which quickly undergoes a reduction reaction with the indium oxide film (In2O3) on the surface of the alloy powder, thereby ensuring the comprehensive brazing performance of the solder paste.
[0038] 5. The high thermal conductivity In-Pb-X alloy low-temperature solder paste manufactured using the method of the present invention has a refrigerated storage period of more than 6 months, and the comprehensive performance of the solder paste remains basically unchanged.
[0039] The no-clean, low-temperature solder paste of the present invention features a scientific design, reasonable formulation, and simple preparation process, making it suitable for a variety of soldering processes. The solder paste has a high melting point, good wettability for metal coatings, is non-corrosive, and leaves little post-soldering residue, making it suitable for soldering silver (alloy) coatings, gold coatings, and copper coatings on electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The differential thermal (melting temperature DSC) curve of the high thermal conductivity In-15Pb-5Ag alloy powder prepared in Example 1;
[0041] Figure 2Electron microscope photograph of the morphology of the high thermal conductivity In-15Pb-5Ag alloy powder prepared in Example 1;
[0042] Figure 3 The preparation process of high thermal conductivity In-15Pb-5Ag alloy solder paste is as shown in Example 1;
[0043] Figure 4 Microscope photo of the high thermal conductivity In-15Pb-5Ag alloy solder paste prepared in Example 1. DETAILED DESCRIPTION
[0044] The high thermal conductivity In-Pb-X alloy low-temperature solder paste of the present invention comprises, by weight percentage, 80.0wt% to 90.0wt% of solder alloy powder, 6.0wt% to 10.0wt% of a highly active soldering flux, and 4.0wt% to 10.0wt% of a coating agent. The solder alloy powder comprises: 14.0wt% to 41.0wt% of Pb, 0wt% to 10wt% of X, the balance being In, and the X element being one or more of Sn, Ag, Au, Bi, Sb, and Cu. The soldering flux comprises: 5wt% to 10% of an active agent, 5wt% to 10% of a surfactant, 2wt% to 8% of a paste-forming agent, 20wt% to 30% of a wetting agent, 2wt% to 5% of a thixotropic agent, and 40wt% to 65% of a solvent. The coating agent comprises: 35wt% to 38% of sodium citrate and 62wt% to 65% of a low-boiling-point solvent.
[0045] The method for preparing the high thermal conductivity In-Pb-X alloy low-temperature solder paste of the present invention is obtained by melting the solder alloy, preparing the solder alloy powder, preparing the flux and preparing the solder paste. The method comprises the following steps:
[0046] (1) Solder alloy melting
[0047] The materials are prepared according to weight percentage: Pb: 14.0-41.0wt%, X: 0-10wt%, In balance, and the alloy is obtained by non-vacuum electromagnetic stirring melting and rapid cooling continuous casting. The heating power is 10-15kw, the refining temperature is 300-350℃, the refining time is 20-30min, and the rapid cooling crystallizer is high-density graphite.
[0048] (2) Preparation of solder alloy powder
[0049] Adopting "inert gas atomization + high-speed centrifugal rotation", using high-purity argon as the atomizing gas, the atomizing temperature is 300℃~340℃, the atomizing gas pressure is 0.2MPa~0.5MPa, the centrifugal speed is 1000~2000n / min, and the atomizing disk is 316L stainless steel, the alloy prepared in step (1) is atomized to obtain alloy powder; after separation by inert gas flow, alloy spherical powders of different particle size ranges are obtained;
[0050] (3) Flux preparation
[0051] Prepare materials according to weight percentage: 5% to 10% of active agent, 5% to 10% of surfactant, 2% to 8% of paste-forming agent, 20% to 30% of wetting agent, 2% to 5% of thixotropic agent and 40% to 65% of solvent; add active agent, paste-forming agent, wetting agent and thixotropic agent to solvent, heat to 50°C to 70°C with stirring, mix evenly after being completely dissolved, and let stand to prepare flux;
[0052] (4) Preparation of coating agent
[0053] Prepare the materials according to weight percentage: 35-38% sodium citrate is added to 62-65% isopropyl alcohol, and ultrasonic stirring is performed at an ultrasonic frequency of 80-100 kHz. After complete dissolution, the mixture is mixed evenly and allowed to stand to obtain a coating agent;
[0054] (5) Solder paste preparation
[0055] The alloy powder obtained in step (2) is immersed in the coating agent obtained in step (4), and the surface of the alloy powder is fully coated by ultrasonic assistance at an ultrasonic frequency of 100 to 120 kHz for 15 to 30 minutes; the high-activity flux obtained in step (3) is then added in proportion, and a vacuum degassing centrifugal stirring method is used, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 800 ~ 1200rpm, stirring time 10 ~ 20min, non-contact, low-pressure alloy solder paste is obtained, and it is put into plastic jars or syringes to obtain high thermal conductivity In-Pb-X alloy low-temperature solder paste.
[0056] The following further describes the no-clean low-temperature solder paste and its preparation method of the present invention in conjunction with an embodiment of specific ingredient calculation.
[0057] Example 1:
[0058] (1) Raw material weighing and solder alloy melting
[0059] X is Ag, and 1500g of Pb, 500g of Ag, and 8000g of In are weighed respectively; the weighed high-purity metal raw materials of Pb, Ag, and In are placed in an alumina crucible, and an alloy is obtained by non-vacuum electromagnetic stirring melting and rapid cooling continuous casting. The heating power is 15 kW. After the materials are completely melted, they are refined at a refining temperature of 320°C and a refining time of 25 minutes. The rapid cooling crystallizer is a high-density graphite; and an alloy ingot is produced.
[0060] (2) Preparation of solder alloy powder
[0061] Adopt "inert gas atomization + high-speed centrifugal rotation", use high-purity argon as atomizing gas, atomizing temperature of 320 ℃, atomizing gas pressure of 0.3MPa, centrifugal speed of 1500n / min, atomizing disk of 316L stainless steel, atomize the alloy prepared in step (1) to prepare alloy powder; after inert gas flow separation, obtain No. 4 (20-38 micron) alloy spherical powder, such as Figure 2 The figure shows the electron microscope photo of the alloy powder morphology of Example 1;
[0062] (3) Flux preparation
[0063] Prepare the following materials by weight: 10% methyltetrahydrophthalic anhydride, 5% stearic acid amide, 5% hydroxyethyl cellulose, 25% cocamidopropyl betaine, 5% PLUS thixotropic agent, and 50% hydrogenated rosin solution (concentration is 50%) + malic acid (wherein the malic acid is 5 wt.%); the total amount of each component is 100%; add the neutral acid anhydride, stearic acid amide, hydroxyethyl cellulose, cocamidopropyl betaine, and PLUS thixotropic agent to a mixed solvent of hydrogenated rosin solution + malic acid (5 wt.%), heat to 70° C. with stirring, wait until completely dissolved, mix evenly, and let stand to prepare a soldering flux;
[0064] (4) Preparation of coating agent
[0065] Prepare the materials according to weight percentage: 35% sodium citrate is added to 65% isopropyl alcohol, and ultrasonic stirring is performed at an ultrasonic frequency of 80 kHz. After complete dissolution, the mixture is mixed evenly and allowed to stand to prepare a coating agent;
[0066] (5) Solder paste preparation
[0067] The alloy powder obtained in step (2) was immersed in the coating agent obtained in step (4), and ultrasonic assistance was used at an ultrasonic frequency of 120KHz for 20min to fully coat the surface of the alloy powder; the high-activity flux obtained in step (3) was then added in proportion, and a vacuum degassing centrifugal stirring method was used, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 1000 rpm, stirring time: 15 min, the alloy solder paste was obtained by non-contact and low pressure, and was put into a plastic can to obtain a high thermal conductivity In-15Pb-5Ag alloy low-temperature solder paste.
[0068] Example 2:
[0069] (1) Raw material weighing and solder alloy melting
[0070] X is selected as Sn element, and 3200g of Pb, 1000g of Sn, and 5800g of In are weighed respectively; the weighed high-purity metal raw materials of Pb, Sn, and In are placed in an alumina crucible, and an alloy is obtained by non-vacuum electromagnetic stirring melting and rapid cooling continuous casting. The heating power is 10 kW. After the materials are completely melted, they are refined at a refining temperature of 300°C and a refining time of 20 minutes. The rapid cooling crystallizer is a high-density graphite. The alloy ingot is then produced;
[0071] (2) Preparation of solder alloy powder
[0072] Adopting "inert gas atomization + high-speed centrifugal rotation", using high-purity argon as the atomizing gas, the atomizing temperature is 300 ° C, the atomizing gas pressure is 0.2 MPa, the centrifugal speed is 1000 n / min, and the atomizing disk is 316L stainless steel, the alloy prepared in step (1) is atomized to obtain alloy powder; after separation by inert gas flow, No. 3 (25-45 microns) alloy spherical powder is obtained;
[0073] (3) Flux preparation
[0074] Prepare materials by weight percentage: 5% hexahydro-4-methylphthalic anhydride, 8% stearic acid amide, 10% hydroxyethyl cellulose, 20% cocamidopropyl betaine, 2% PLUS thixotropic agent, and 55% hydrogenated rosin solution (concentration is 50%) + malic acid (of which malic acid is 5 wt.%); the total amount of each component is 100%; add neutral acid anhydride, stearic acid amide, hydroxyethyl cellulose, cocamidopropyl betaine, and PLUS thixotropic agent to a mixed solvent of hydrogenated rosin solution + malic acid (5 wt.%), heat to 60° C. with stirring, wait until completely dissolved, mix evenly, and let stand to prepare a soldering flux;
[0075] (4) Preparation of coating agent
[0076] Prepare the materials according to weight percentage: 38% sodium citrate is added to 62% isopropyl alcohol, and ultrasonic stirring is performed at an ultrasonic frequency of 100KHz. After complete dissolution, the mixture is mixed evenly and allowed to stand to obtain a coating agent;
[0077] (5) Solder paste preparation
[0078] The alloy powder obtained in step (2) was immersed in the coating agent obtained in step (4), and ultrasonic assistance was used at an ultrasonic frequency of 100 KHz for 15 min to fully coat the surface of the alloy powder; the high-activity flux obtained in step (3) was then added in proportion, and vacuum degassing and centrifugal stirring were used, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 800 rpm, stirring time: 10 min, the alloy solder paste is obtained by non-contact and low pressure, and is put into a plastic can to obtain a high thermal conductivity In-32Pb-10Sn alloy low-temperature solder paste.
[0079] Example 3:
[0080] (1) Raw material weighing and solder alloy melting
[0081] X selects Au and Sb elements, and weighs 3500g of Pb, 300g of Au, 300g of Sb, and 5900g of In respectively; the weighed high-purity metal raw materials of Pb, Au, Sb, and In are placed in an alumina crucible, and alloys are obtained by non-vacuum electromagnetic stirring melting and rapid cooling continuous casting. The heating power is 15 kW. After the materials are completely melted, they are refined at a refining temperature of 350°C and a refining time of 30 minutes. The rapid cooling crystallizer is a high-density graphite; and alloy ingots are produced.
[0082] (2) Preparation of solder alloy powder
[0083] Adopting "inert gas atomization + high-speed centrifugal rotation", using high-purity argon as the atomizing gas, the atomizing temperature is 340 ° C, the atomizing gas pressure is 0.2 MPa, the centrifugal speed is 1000 n / min, and the atomizing disk is 316L stainless steel, the alloy prepared in step (1) is atomized to obtain alloy powder; after separation by inert gas flow, No. 4 (20-38 microns) alloy spherical powder is obtained;
[0084] (3) Flux preparation
[0085] Prepare the following materials by weight: 6% succinic anhydride, 6% stearic acid amide, 8% hydroxyethyl cellulose, 30% cocamidopropyl betaine, 5% PLUS thixotropic agent, and 45% hydrogenated rosin solution (concentration is 50%) + malic acid (of which malic acid is 5 wt.%); the total amount of each component is 100%; add the neutral acid anhydride, stearic acid amide, hydroxyethyl cellulose, cocamidopropyl betaine, and PLUS thixotropic agent to a mixed solvent of hydrogenated rosin solution + malic acid (5 wt.%), heat to 50° C. with stirring, wait until completely dissolved, mix evenly, and let stand to prepare a soldering flux;
[0086] (4) Preparation of coating agent
[0087] Prepare the materials according to weight percentage: 36% sodium citrate is added to 64% isopropyl alcohol, and ultrasonic stirring is performed at an ultrasonic frequency of 90 kHz. After complete dissolution, the mixture is mixed evenly and allowed to stand to prepare a coating agent;
[0088] (5) Solder paste preparation
[0089] The alloy powder obtained in step (2) was immersed in the coating agent obtained in step (4), and ultrasonic assistance was used at an ultrasonic frequency of 120KHz for 30 minutes to fully coat the surface of the alloy powder; the high-activity flux obtained in step (3) was then added in proportion, and a vacuum degassing centrifugal stirring method was used, with a vacuum degree of <1.0×10 -1Pa, stirring speed: 1200rpm, stirring time: 20min, alloy solder paste is obtained by non-contact and low pressure, and is loaded into a needle tube to obtain high thermal conductivity In-35Pb-3Au-3Sb alloy low-temperature solder paste.
[0090] Example 4:
[0091] (1) Raw material weighing and solder alloy melting
[0092] X is selected as Bi element, and 4100g of Pb, 500g of Bi, and 5400g of In are weighed respectively; the weighed high-purity metal raw materials of Pb, Bi, and In are placed in an alumina crucible, and an alloy is obtained by non-vacuum electromagnetic stirring melting and rapid cooling continuous casting. The heating power is 10kW. After the materials are completely melted, they are refined at a refining temperature of 300°C and a refining time of 20 minutes. The rapid cooling crystallizer is a high-density graphite. The alloy ingot is then produced;
[0093] (2) Preparation of solder alloy powder
[0094] Adopting "inert gas atomization + high-speed centrifugal rotation", using high-purity argon as the atomizing gas, the atomizing temperature is 300 ° C, the atomizing gas pressure is 0.5 MPa, the centrifugal speed is 2000 n / min, and the atomizing disk is 316L stainless steel, the alloy prepared in step (1) is atomized to obtain alloy powder; after separation by inert gas flow, No. 6 (10-20 microns) alloy spherical powder is obtained;
[0095] (3) Flux preparation
[0096] Prepare the following materials by weight: 10% methyltetrahydrophthalic anhydride, 8% stearic acid amide, 5% hydroxyethyl cellulose, 30% cocamidopropyl betaine, 5% PLUS thixotropic agent, and 42% hydrogenated rosin solution (concentration is 50%) + malic acid (of which malic acid is 5 wt.%); the total amount of each component is 100%; add the neutral acid anhydride, stearic acid amide, hydroxyethyl cellulose, cocamidopropyl betaine, and PLUS thixotropic agent to a mixed solvent of hydrogenated rosin solution + malic acid (5 wt.%), heat to 50° C. to 70° C. with stirring, and after complete dissolution, mix evenly and let stand to prepare a soldering flux;
[0097] (4) Preparation of coating agent
[0098] Prepare the materials according to weight percentage: 35% sodium citrate is added to 65% isopropyl alcohol, and ultrasonic stirring is performed at an ultrasonic frequency of 80 kHz. After complete dissolution, the mixture is mixed evenly and allowed to stand to prepare a coating agent;
[0099] Step (5) Solder paste preparation
[0100] The alloy powder obtained in step (2) was immersed in the coating agent obtained in step (4), and ultrasonic assistance was used at an ultrasonic frequency of 120KHz for 30 minutes to fully coat the surface of the alloy powder; the high-activity flux obtained in step (3) was then added in proportion, and a vacuum degassing centrifugal stirring method was used, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 1200rpm, stirring time: 20min, the alloy solder paste is obtained by non-contact and low pressure, and is loaded into a needle tube to obtain a high thermal conductivity In-41Pb-5Bi alloy low-temperature solder paste.
[0101] Example 5:
[0102] (1) Raw material weighing and solder alloy melting
[0103] X selects Sn, Ag, and Cu elements, and weighs 1400g of Pb, 750g of Sn, 100g of Ag, 50g of Cu, and 7700g of In, respectively; the weighed high-purity metal raw materials of Pb, Sn, Ag, Cu, and In are placed in an alumina crucible, and an alloy is obtained by non-vacuum electromagnetic stirring melting and rapid cooling continuous casting. The heating power is 15 kW. After the materials are completely melted, they are refined at a refining temperature of 350°C and a refining time of 20 minutes. The rapid cooling crystallizer is high-density graphite; and an alloy ingot is made.
[0104] (2) Preparation of solder alloy powder
[0105] The alloy powder was obtained by atomizing the alloy obtained in step (1) by adopting "inert gas atomization + high-speed centrifugal rotation" with high-purity argon as the atomizing gas, the atomizing temperature being 300°C, the atomizing gas pressure being 0.3 MPa, the centrifugal speed being 1500 n / min, and the atomizing disk being 316L stainless steel; and No. 4 alloy spherical powder (20-38 microns) was obtained by separation by inert gas flow.
[0106] (3) Flux preparation
[0107] Prepare the following materials by weight: 10% methyl nadic anhydride, 8% stearic acid amide, 10% hydroxyethyl cellulose, 30% cocamidopropyl betaine, 2% PLUS thixotropic agent, and 40% hydrogenated rosin solution (concentration is 50%) + malic acid (of which malic acid is 5 wt.%); the total amount of each component is 100%; add the neutral acid anhydride, stearic acid amide, hydroxyethyl cellulose, cocamidopropyl betaine, and PLUS thixotropic agent to a mixed solvent of hydrogenated rosin solution + malic acid (5 wt.%), heat to 70° C. with stirring, wait until completely dissolved, mix evenly, and let stand to prepare a soldering flux;
[0108] (4) Preparation of coating agent
[0109] Prepare the materials according to weight percentage: 38% sodium citrate is added to 62% isopropyl alcohol, and ultrasonic stirring is performed at an ultrasonic frequency of 100KHz. After complete dissolution, the mixture is mixed evenly and allowed to stand to obtain a coating agent;
[0110] (5) Solder paste preparation
[0111] The alloy powder obtained in step (2) was immersed in the coating agent obtained in step (4), and ultrasonic assistance was used at an ultrasonic frequency of 100 KHz for 15 min to fully coat the surface of the alloy powder; the high-activity flux obtained in step (3) was then added in proportion, and vacuum degassing and centrifugal stirring were used, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 800 rpm, stirring time: 20 min, the alloy solder paste was obtained by non-contact and low pressure, and loaded into a needle tube to obtain a high thermal conductivity In-14Pb-7.5Sn-1Ag-0.5Cu alloy low-temperature solder paste.
[0112] The thermally conductive In-Pb-X alloy low-temperature solder pastes prepared in Examples 1-5 were tested for soldering temperature, working life, wetting performance, and post-soldering residue. The test data are shown in Table 1.
[0113] Table 1 Performance of high thermal conductivity In-Pb-X alloy low temperature solder paste in Examples 1 to 5
[0114] Appearance Melting temperature Working life Spreading coefficient Post-weld residue Example 1 No powder separation 149~152℃ 192 days 94.9% No, no cleaning Example 2 No powder separation 132~135℃ 189 days 93.2% Less, no need to clean Example 3 No powder separation 181~183℃ 187 days 94.5% Less, no need to clean Example 4 No powder separation 124~150℃ 185 days 93.9% No, no cleaning Example 5 No powder separation 142~156℃ 182 days 93.8% Less, no need to clean
[0115] like Figure 1 As shown in FIG1 , the differential thermal curve of the high thermal conductivity In-15Pb-5Ag alloy powder prepared in Example 1 is shown. It can be seen from the figure that the melting temperature of the In-15Pb-5Ag alloy obtained by adopting the alloy proportion and preparation method designed in the present invention is 149.09~152.5°C, the exothermic peak curve is smooth and obvious, and there is no low melting point phase precipitation and phase change. Considering the test accuracy of the equipment, the melting point of the alloy can be regarded as the eutectic temperature of 150°C, which meets the design requirements of the present invention.
[0116] like Figure 2 As shown in FIG1 , the morphology of the high thermal conductivity In-15Pb-5Ag alloy powder prepared in Example 1 is obtained by an electron microscope. As can be seen from the figure, the In-15Pb-5Ag alloy powder obtained by the preparation method of the present invention has a narrow particle size range, the sphere size tends to be consistent, there is little macromolecular agglomeration phenomenon, and the sphericity rate is greater than 95%, which meets the design requirements of the present invention.
[0117] like Figure 3As shown in the figure, the preparation process of high thermal conductivity In-15Pb-5Ag alloy solder paste prepared in Example 1 is shown. As can be seen from the figure, the In-based solder paste preparation method developed by this patent successfully solves the problems of drying out and particle coarsening of In-based solder paste. Through ultrasound + coating + matching flux design, the refrigerated storage period of In-based solder paste exceeds 6 months, the comprehensive performance of the solder paste is basically unchanged, the post-soldering residue is small, and it is easy to clean, meeting the design requirements of the present invention.
[0118] like Figure 4 As shown in the figure, a real-life photograph of the high thermal conductivity In-15Pb-5Ag alloy solder paste prepared in Example 1 is taken under a microscope. As can be seen from the figure, the alloy solder paste prepared by the "non-contact + low-pressure" preparation method disclosed in the present invention does not deform into a spherical shape due to stirring during the paste stirring process, and the surface of the powder particles is coated with flux, thereby avoiding oxidation and moisture absorption and deterioration problems during the solder paste preparation process, thereby meeting the design requirements of the present invention.
[0119] The low-temperature solder paste of the invention has a high melting temperature, good wettability to metal coatings, good soldering processability, and a long working life, and is suitable for soft soldering of silver (alloy) coatings, gold coatings, and copper coatings of electronic devices.
[0120] The high thermal conductivity In-Pb-X alloy low-temperature solder paste of the present invention has a low melting point, a low brazing temperature, high thermal conductivity, a high soldering rate, good wettability to the gold-plated layer, good brazing processability, and is suitable for low-temperature packaging of electronic devices.
[0121] The above embodiments only illustrate the embodiments of the no-clean low-temperature solder paste of the present invention. In the above technical solutions of the present invention, the metal content in the solder alloy and the content of each component in the flux can be freely selected within the prescribed ranges and are not listed here one by one. Therefore, the technical solutions included in the above description should be regarded as illustrative and not intended to limit the patent application of the present invention.
Claims
1. A high thermal conductivity In-Pb-X alloy low-temperature solder paste, characterized by: The invention comprises: 80.0wt% to 90.0wt% of solder alloy powder, 6.0wt% to 10.0wt% of high-activity flux and 4.0wt% to 10.0wt% of coating agent; the composition of the solder alloy powder is: Pb: 14.0wt% to 41.0wt%, X: 0wt% to 10wt%, the balance is In, and the X element is one or more of Sn, Ag, Au, Bi, Sb and Cu.
2. The high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 1, characterized in that: The solder alloy powder contains: Pb: 15.0-35.0 wt%, X: 1-10 wt%, and the balance is In.
3. The high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 1, characterized in that: The highly active soldering flux comprises: 5wt% to 10wt% of an active agent, 5wt% to 10wt% of a surfactant, 2wt% to 8wt% of a paste-forming agent, 20wt% to 30wt% of a wetting agent, 2wt% to 5wt% of a thixotropic agent and 40wt% to 65wt% of a solvent.
4. The high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 3, characterized in that: The active agent is a neutral acid anhydride, which is one of methyltetrahydrophthalic anhydride, hexahydro-4-methylphthalic anhydride, methylnadic anhydride, dodecenylsuccinic anhydride and succinic anhydride; the surfactant is stearic acid amide; the paste-forming agent is hydroxyethyl cellulose; the wetting agent is cocoamidopropyl betaine; the thixotropic agent is PLUS thixotropic agent; and the solvent is hydrogenated rosin solution + malic acid, wherein the malic acid content is 5wt%.
5. The high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 1, characterized in that: The coating agent comprises: 35-38 wt% of sodium citrate and 62-65 wt% of a low boiling point solvent.
6. The method for preparing a high thermal conductivity In-Pb-X alloy low-temperature solder paste according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Solder alloy smelting: Prepare the materials according to weight percentage, Pb: 14.0-41.0wt%, X: 0-10wt%, In balance, X element is one or more of Sn, Ag, Au, Bi, Sb and Cu, and use non-vacuum electromagnetic stirring melting and rapid cooling continuous casting to obtain the alloy; (2) Preparation of solder alloy powder: The alloy prepared in step (1) is atomized to obtain spherical alloy powder by using a combined atomization method of "inert gas atomization + high-speed centrifugal rotation", and then an inert gas flow separation method is used to obtain alloy powders of different particle size ranges; (3) Preparation of high-activity soldering flux: Prepare the materials by weight percentage, 5% to 10% of active agent, 5% to 10% of surfactant, 2% to 10% of paste-forming agent, 20% to 30% of wetting agent, 2% to 5% of thixotropic agent and 40% to 65% of solvent, add the active agent, surfactant, paste-forming agent, wetting agent and thixotropic agent to the solvent, heat and stir, mix until completely dissolved, and let it stand to prepare the soldering flux; (4) Preparation of coating agent: Prepare the materials according to weight percentage, add 35-38% sodium citrate into 62-65% isopropyl alcohol, stir with ultrasonic, and after complete dissolution, mix evenly and let stand to prepare the coating agent; (5) Preparation of solder paste: The alloy powder obtained in step (2) is immersed in the coating agent obtained in step (4), and the surface of the alloy powder is fully coated using ultrasonic assistance; then the high-activity flux obtained in step (3) is added in proportion, and the coated powder and the flux are mixed evenly in a contactless and low-pressure manner using a vacuum degassing centrifugal stirring method to obtain a high thermal conductivity In-Pb-X alloy low-temperature solder paste.
7. The method for preparing a high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 6, characterized in that: A non-vacuum medium-frequency induction continuous casting furnace is used to melt the solder alloy. The heating power is 10-15 kW, the refining temperature is 300-350°C, the refining time is 20-30 min, and the rapid cooling crystallizer is high-density graphite.
8. The method for preparing a high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 6, characterized in that: The atomization temperature is 300°C to 340°C, the inert gas is high-purity argon, the atomization gas pressure is 0.2MPa to 0.5MPa, the centrifugal speed is 1000 to 2000n / min, and the atomizing disk is 316L stainless steel; the particle size range of the alloy powder is 25 to 45 microns, 20 to 38 microns, 15 to 25 microns or 10 to 20 microns; when preparing the flux, the heating temperature is 50°C to 70°C; when preparing the coating agent, the ultrasonic frequency is 80 to 100KHz.
9. The method for preparing a high thermal conductivity In-Pb-X alloy low-temperature solder paste according to claim 6, characterized in that: The solder paste is prepared by firstly ultrasonically coating the alloy powder at an ultrasonic frequency of 100-120 KHz for 15-30 min; then centrifugally stirring the powder with the flux by vacuum degassing to prepare the paste, with a vacuum degree of <1.0×10 -1 Pa, stirring speed: 800-1200 rpm, stirring time 10-20 min, prepare the alloy solder paste, and put it into a plastic jar or syringe.
10. Use of the high thermal conductivity In-Pb-X alloy low-temperature solder paste according to any one of claims 1 to 5 in an assembly welding process for electronic components, surface mount components and / or electronic circuits.